Respostas

A melhor resposta!
2014-07-10T09:48:10-03:00
Simplifique ao máximo a fração:
           em que x ≠ -1

  x³ + x² - x - 1          (x+1)(x+1)(-1)            (x+1)(x+1)(x-1) : (x+1)(x+1)        x -1
------------------- =  ----------------------- =   ------------------------------------ = ---------- = x - 1
   x² + 2x + 1             (x+1)(x+1)                      (x+1)(x+1)   :(x+1)(x+1)           1

para  x 
≠ - 1 
e
Q(x) = quociente   x - 1
então   
x - 1 igualar a ZERO
X - 1 = 0
x = + 1


OU  outra maneira de fazer


   x³ + x² - x - 1      |___x² + 2x + 1_______
 - x³ -2x²  -x                x - 1
--------------
  0   -x²  - 2x - 1
      +x²  +2x  +1
     ----------------
        0     0    0


2 5 2